Fracture response of fiber-reinforced sodium carbonate activated slag mortars - Akturk, Busra; Akca, Abdullah H.; Kizilkanat, Ahmet B. (ELSEVIER SCI LTD, 2020)
Sodium carbonate-activated slag (NCAS) is getting attention with its environmental benefits among the other alkali-activated materials. However, long setting time and the brittleness of these materials are still an issue that needs to be tailored. In this study, the matrix phase of NCAS was strengthened with the aid of two modifiers: calcium hydroxide (CH) and sodium hydroxide (NH), and significant improvement in both setting time and mechanical properties was achieved. Moreover, polypropylene and steel fibers were used in order to enhance the fracture properties of NCAS mortars. The results showed that fracture properties are improved with the modifiers and the contribution of CH was much more pronounced. Fiber reinforcement improved the fracture properties, the contribution of steel fibers was significant. After the flexural test, crack patterns were evaluated and also the adhesion between the matrix and fiber was examined in a scanning electron microscope. It was found that the type of fiber and fiber-matrix bonding mechanism are more effective in the improvement of the fracture properties rather than the matrix features. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Fracture parameters; Fiber-matrix adhesion; Fiber reinforcement; Sodium carbonate; Alkali-activated slag; QUASI-BRITTLE FRACTURE; DOUBLE-K CRITERION; MECHANICAL-PROPERTIES; CEMENTITIOUS COMPOSITE; FLEXURAL PERFORMANCE; CRACK-PROPAGATION; SYNTHETIC-FIBERS; HYBRID STEEL; PART I; BEHAVIOR; Construction & Building Technology; Engineering; Materials Science